Issues in multiple directorship and firm’s cash holding: a conceptual paper - Ihelsa Rumondang Siregar; Chyntia Afriani Utama (President University, 2022)
This paper aims to explain the issues in board practices in corporate governance. The board practices that this paper wants to uncover are multiple positions by the director in a company. This paper specifically wants to discuss multiple positions held by the commissioners and directors in a public company in Indonesia. The method used for this conceptual paper is based on a literature review, journal articles, previous studies, online news related to the topic, and regulation related to the multiple directorships in Indonesia. Multiple directorships are when a director of a firm hold two or more position on another firm’s board. The practice of multiple directorships has two points of view; the first point of view told that multiple directorships are one of the elements in board practice that is important to create good corporate governance in reducing agency problems. But another point of view said that multiple directorships create a busy board, which results in an “over-committed” board. Although there is a lot of research on multiple directorship topics, such as the effect of multiple directorships on firm performance and firm value, further research is needed to uncover the effect of multiple directorships in reducing agency problems in a firm, such as an agency problem in a firm’s cash holding.